Dexketoprofen trometamol plaster and preparation method thereof
Ketoprofen nanofibers were prepared by electrospinning technology and coated with titanium dioxide and polyN-isopropyl acrylamide. The matrix sol was prepared in combination with the sol-gel method to form dextroketoprofen turatamide paste, which solved the problem of unstable ketoprofen paste under light and significantly improved its light stability and efficacy.
Patent Information
- Application Number
- CN202510079523.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-18
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-01-18
AI Technical Summary
The existing ketoprofen paste has problems of unstable and easy decomposition under light, which affects its use effect.
Ketoprofen nanofibers were prepared by electrospinning technology, and their outer walls were coated with titanium dioxide and polyN-isopropyl acrylamide, and matrix sol was prepared in combination with sol-gel method to form dextroketoprofen tromethamol paste.
It significantly improves the light stability of ketoprofen paste, extends the effective use time of the drug, and shortens the pain-relieving time through the addition of ropivacaine, and improves the storage stability of the drug.
Smart Images

Figure BDA0005248099550000111 
Figure BDA0005248099550000121 
Figure BDA0005248099550000132
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of pharmaceutical chemistry, and in particular to a dexketoprofen tromethamine plaster and a preparation method thereof. Background Art
[0002] Ketoprofen is a nonsteroidal anti-inflammatory analgesic, also known as ibuprofen ketone. Its main function is to relieve mild to moderate pain, including headache, toothache, joint pain, muscle pain, etc. Prostaglandins can sensitize nerve endings, leading to the occurrence of pain. Ketoprofen reduces the synthesis of prostaglandins, thereby reducing pain. Ketoprofen can also relieve discomfort caused by inflammation and is suitable for inflammatory diseases such as arthritis and rheumatoid arthritis. Ketoprofen exerts its anti-inflammatory effect by inhibiting the activity of cyclooxygenase (COX). COX is a key enzyme that participates in the conversion of arachidonic acid to prostaglandins. Prostaglandins are a class of pro-inflammatory mediators that participate in the occurrence of inflammatory reactions. Ketoprofen inhibits the activity of COX, thereby reducing inflammatory symptoms. Ketoprofen also has the effect of lowering body temperature and is suitable for discomfort caused by fever. During the fever process, white blood cells release prostaglandins, which cause the body temperature to rise by affecting the hypothalamic temperature regulation center. Ketoprofen inhibits the synthesis of prostaglandins, reduces the stimulation of prostaglandins on the hypothalamic temperature regulation center, and thus alleviates the symptoms of fever.
[0003] Ketoprofen gel or patch is a topical drug with broad application prospects in recent years. Ketoprofen gel uses ketoprofen as the main active ingredient. It acts directly on the skin surface and local tissues through application and massage, thereby penetrating the skin and releasing ketoprofen at the site of inflammation for local treatment of pain and inflammation. The transdermal administration used by ketoprofen gel is a non-invasive way to deliver drugs into the body through the skin. Unlike traditional direct administration routes, transdermal administration does not require the use of needle injections and does not involve passage through the gastrointestinal tract. Small molecule drugs can usually use intracellular pathways to pass through the epidermal stratum corneum, so there will be no first-pass metabolism that leads to drug loss, and the drug can be delivered without interference from pH, enzymes, and intestinal bacteria.
[0004] A series of prior arts with publication numbers CN118526444A, CN116747208A, CN103156803A and CN110693860A are all dedicated to providing ketoprofen medicines for external use.
[0005] However, the problems with these prior arts are that the active ingredient of ketoprofen is unstable and easily decomposed under light. For ketoprofen used as a patch, it is particularly important to improve its light stability. Summary of the invention
[0006] One of the problems solved by the present invention is how to provide a dexketoprofen patch with better photostability.
[0007] To solve at least one of the above problems, the present invention provides a method for preparing a dexketoprofen tromethamine patch, the preparation method comprising:
[0008] S100, preparing ketoprofen nanofibers by electrospinning using raw materials including dexketoprofen tromethamine, a first polyacrylic acid, poly-N-isopropylacrylamide, chitosan and titanium dioxide;
[0009] S200, using raw materials including ropivacaine, L-phenylalanine, a second polyacrylic acid and tetraethyl orthosilicate to prepare a matrix sol by a sol-gel method;
[0010] S300, mixing the ketoprofen nanofibers and the matrix sol, and performing gelation treatment to prepare a dexketoprofen tromethamine patch.
[0011] In any of the above technical solutions, S100 specifically includes:
[0012] S110, mixing raw materials including dexketoprofen tromethamine, a first polyacrylic acid, polyvinyl pyrrolidone, ethanol, polyvinyl alcohol and water to obtain a core layer spinning solution;
[0013] S120, mixing raw materials including titanium dioxide, chitosan, poly (N-isopropylacrylamide), methylcellulose, polylactic acid, water and hexafluoroisopropanol to obtain a shell spinning solution;
[0014] S130, injecting the core layer spinning solution and the shell layer spinning solution into a coaxial electrospinning device, and performing electrospinning to obtain ketoprofen nanofibers;
[0015] The inner core of the ketoprofen nanofiber contains dexketoprofen tromethamine, and the outer wall contains poly (N-isopropylacrylamide) and titanium dioxide.
[0016] In any of the above technical schemes, S110 specifically includes: first mixing polyvinyl alcohol and half of the water in a first container according to a mass ratio of dexketoprofen tromethamine: first polyacrylic acid: polyvinyl pyrrolidone: ethanol: polyvinyl alcohol: water = (0.2-0.4): (8-12): (8-12): (16-20): (16-20): 100, then adding a uniform mixture of dexketoprofen tromethamine and ethanol to the first container for mixing, finally swelling the first polyacrylic acid and polyvinyl pyrrolidone in the other half of the water and adding them to the first container for mixing, magnetically stirring for 8h to 10h, and standing for 1.5h to 2h for degassing to obtain a core layer spinning solution.
[0017] In any of the above technical solutions, S120 specifically includes: first mixing methyl cellulose, polylactic acid and hexafluoroisopropanol in a second container according to a mass ratio of titanium dioxide: chitosan: poly N-isopropylacrylamide: methyl cellulose: polylactic acid: water: hexafluoroisopropanol = (0.2-0.6): (4-6): (8-12): (8-12): (14-18): (40-50): 100, and then adding a uniform mixture of titanium dioxide, chitosan, poly N-isopropylacrylamide and water into the second container, mixing, magnetically stirring for 2h to 4h, and standing for 0.5h to 2h for degassing to obtain a shell spinning solution;
[0018] In any of the above technical schemes, S130 specifically includes: injecting the core layer spinning solution and the shell layer spinning solution into a coaxial electrospinning device, controlling the injection flow rate of the core layer spinning solution to 0.7mL / h to 0.8mL / h, controlling the injection flow rate of the shell layer spinning solution to 0.3mL / h to 0.4mL / h, performing electrospinning under a voltage condition of 12kV to 14kV, receiving with tin foil at a receiving distance of 18cm to 20cm, and vacuum drying at room temperature for 18h to 24h after receiving, to obtain ketoprofen nanofibers.
[0019] In any of the above technical solutions, S200 specifically includes:
[0020] S210, using raw materials including ropivacaine, L-phenylalanine, a second polyacrylic acid, tetraethyl orthosilicate, ethanol and water, using hydrochloric acid as a catalyst, and obtaining a matrix sol through a sol-gel reaction.
[0021] In any of the above technical solutions, S210 specifically includes: first, ropivacaine, tetraethyl orthosilicate and ethanol are uniformly mixed in a third container according to a mass ratio of ropivacaine: L-phenylalanine: second polyacrylic acid: tetraethyl orthosilicate: ethanol: water = (1-1.5): (2-3): (6-8): (8-10): (30-35): 100, and then a uniform mixture of L-phenylalanine, the second polyacrylic acid and water is added to the third container for mixing, an aqueous solution of hydrochloric acid is added dropwise to adjust the pH value to 4 to 5, and magnetic stirring is performed for 3h to 4h to obtain a matrix sol.
[0022] In any of the above technical solutions, S300 specifically includes:
[0023] S310, mixing and dispersing the ketoprofen nanofibers in the matrix sol uniformly to obtain a ketoprofen sol;
[0024] S320, soaking the ketoprofen sol in anhydrous ethanol for aging for 30 to 36 hours, taking it out, washing it, and drying it to obtain a dexketoprofen tromethamine patch.
[0025] In any of the above technical solutions, in S310, the mass ratio of ketoprofen nanofibers to matrix sol is (40-60):100.
[0026] The present invention also provides a dexketoprofen tromethamine patch, which is obtained by using the preparation method of any of the above technical solutions.
[0027] Beneficial Effects
[0028] The preparation method of the present invention first adopts the raw material comprising dexketoprofen tromethamine, a first polyacrylic acid, poly-N-isopropylacrylamide, chitosan and titanium dioxide, and prepares the ketoprofen nanofiber by electrostatic spinning. Then adopts the raw material comprising ropivacaine, L-phenylalanine, a second polyacrylic acid and tetraethyl orthosilicate, and prepares the matrix sol by a sol-gel method. Finally, the ketoprofen nanofiber and the matrix sol are mixed, and gelation is carried out to prepare the dexketoprofen tromethamine patch.
[0029] Dexketoprofen tromethamine is an over-the-counter drug for treating joint swelling and pain caused by rheumatoid arthritis, rheumatoid arthritis and osteoarthritis. Its plaster dosage form helps release the drug to the affected area and is suitable for long-term administration and treatment.
[0030] Compared with the ketoprofen patch of the gel system in the prior art, the present invention prepares dexketoprofen tromethamine-loaded nanofibers by electrospinning, and uses titanium dioxide as a sunscreen to protect the dexketoprofen tromethamine.
[0031] Ropivacaine can shorten the analgesic effect time of dexketoprofen tromethamine patch, and L-phenylalanine can protect dexketoprofen tromethamine and further improve its storage stability.
[0032] In addition, compared with the water-soluble polymer gel in the prior art, the present invention adopts an inorganic gel system of silicon dioxide, which has higher mechanical strength, thermal stability and chemical stability, and can effectively protect the dexketoprofen tromethamine-loaded nanofibers inside. DETAILED DESCRIPTION
[0033] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the following is a detailed description of the specific embodiments of the present invention.
[0034] Unless otherwise specified, the reagents and raw materials used in the present invention can be purchased through commercial channels. The experimental methods in the following examples without specifying specific conditions are selected according to conventional methods and conditions, or according to the product specifications.
[0035] The preparation method of the dexketoprofen tromethamine patch of the present invention comprises:
[0036] S100, preparing ketoprofen nanofibers by electrospinning using raw materials including dexketoprofen tromethamine, a first polyacrylic acid, poly-N-isopropylacrylamide, chitosan and titanium dioxide;
[0037] S200, using raw materials including ropivacaine, L-phenylalanine, a second polyacrylic acid and tetraethyl orthosilicate to prepare a matrix sol by a sol-gel method;
[0038] S300, mixing the ketoprofen nanofibers and the matrix sol, and performing gelation treatment to prepare a dexketoprofen tromethamine patch.
[0039] Dexketoprofen is the dextrorotatory form of ketoprofen and is the active ingredient in the ketoprofen racemate. Its effect is equivalent to twice that of the same dose of ketoprofen. The use of dexketoprofen can reduce the toxic and side effects of the levorotatory form (ineffective ingredient) of ketoprofen. Dexketoprofen is generally used in the form of tromethamine salt.
[0040] Although the active ingredient content of dexketoprofen tromethamine is high, its disadvantage is that the photostability is poor. Ketoprofen drugs can undergo photolysis reaction rapidly under sunlight irradiation. This is because the carbonyl group in the molecular structure of ketoprofen is connected with two benzene rings, so that the carbonyl group and the two benzene rings are highly conjugated, causing the n-π transition energy to be very low, easily generating highly active triplet states, thereby inducing photolysis reaction. For the ketoprofen plaster as a topical preparation for transdermal administration, improving its photostability is particularly important.
[0041] In order to improve the light stability of ketoprofen drugs, the present invention chooses to add titanium dioxide sunscreen in ketoprofen drugs. The size of titanium dioxide particles is usually between 10 nanometers and 1 micron, which is equivalent to the wavelength of visible light. When light encounters titanium dioxide particles, the light will be scattered multiple times on the surface of the particles. This scattering effect makes the propagation path of light in the medium complicated and difficult to penetrate, thereby effectively reducing the transmittance of light. In addition, titanium dioxide has a certain absorption capacity in the ultraviolet light region. It can absorb ultraviolet light and convert it into heat energy. This absorption effect can prevent ultraviolet light from entering the blocked object. Finally, the refractive index of titanium dioxide is relatively high. When light is injected into titanium dioxide from a medium with a lower refractive index, refraction will occur, and the propagation direction of the light will change. This refraction effect also helps to reduce the transmittance of light, thereby enhancing the light shielding effect. Therefore, the present invention utilizes the above-mentioned characteristics of titanium dioxide to improve the light stability of dexketoprofen tromethamine.
[0042] Ketoprofen and water-soluble polymer compounds, solvents and other adjuvants are formulated into a gel system plaster, which is a common way to prepare ketoprofen plaster in the prior art. However, the half-life of ketoprofen is relatively short, and there is a large fluctuation in the drug release rate of ketoprofen, which cannot ensure that the drug effect is stable. The ketoprofen plaster of a single gel system, its active ingredient is easily absorbed, but releases too fast, causing its sustained release effect to be less than ideal. For this reason, the present invention is prepared as drug-loaded fiber by electrostatic spinning by dexketoprofen tromethamine patch, and then the drug-loaded fiber is mixed in the gel system, ensuring that dexketoprofen tromethamine is released more steadily.
[0043] The onset time of oral ketoprofen is usually 0.5 to 2 hours after taking the medicine. Due to the long analgesic onset time of ketoprofen, there is a solution in the prior art that coordinates the effect of ketoprofen with local anesthetics (such as prilocaine, tetracaine, bupivacaine, etc.).
[0044] Among the many local anesthetics, ropivacaine is one of the most widely used long-acting local anesthetics in clinical practice. It has a rapid onset of action, a long duration, relatively low toxicity to the nervous system, and high safety. In addition to the anesthetic effect, ropivacaine also has an analgesic effect, especially when used in small doses, it can have a local analgesic effect.
[0045] Therefore, the present invention adopts ropivacaine to be compounded with dexketoprofen tromethamine, utilizes ropivacaine to flow into the neurofibroma by blocking sodium ion, produces reversible blockage to the impulse conduction along the nerve fiber, thereby produces the principle of anesthetic effect, and ketoprofen synergistic effect.The onset time of ropivacaine is about about 10 minutes, will be added in the gel matrix, so that it can be quickly released and effective when used.Thus, the present invention compounds ropivacaine with ketoprofen, can make the ketoprofen that the present invention obtains play a better analgesic effect in the treatment of pains such as arthritis, make up the deficiency that the analgesic onset of ketoprofen itself is slow.
[0046] In some implementations of the present invention, S100 specifically includes:
[0047] S110, mixing raw materials including dexketoprofen tromethamine, a first polyacrylic acid, polyvinyl pyrrolidone, ethanol, polyvinyl alcohol and water to obtain a core layer spinning solution;
[0048] S120, mixing raw materials including titanium dioxide, chitosan, poly (N-isopropylacrylamide), methylcellulose, polylactic acid, water and hexafluoroisopropanol to obtain a shell spinning solution;
[0049] S130, injecting the core layer spinning solution and the shell layer spinning solution into a coaxial electrospinning device, and performing electrospinning to obtain ketoprofen nanofibers;
[0050] The inner core of the ketoprofen nanofiber contains dexketoprofen tromethamine, and the outer wall contains poly (N-isopropylacrylamide) and titanium dioxide.
[0051] The purpose of the above steps is to prepare a double-layer composite fiber with dexketoprofen tromethamine as the inner core and titanium dioxide and poly-N-isopropylacrylamide as the outer wall protection through the process of coaxial electrospinning. Thus, titanium dioxide can be evenly coated on the outer wall periphery of the inner core of ketoprofen nanofibers, and the influence of light on dexketoprofen tromethamine can be better reduced.
[0052] In addition, poly (N-isopropylacrylamide) is a thermosensitive polymer material. The thermosensitivity of poly (N-isopropylacrylamide) originates from the hydrophilic acylamino group and hydrophobic isopropyl group on its macromolecular chain. At low temperatures, hydrogen bonds are formed between the acylamino group and the water molecules, making poly (N-isopropylacrylamide) hydrophilic and homogeneous. As the temperature rises, the hydrogen bonds are destroyed and the interaction between the hydrophobic isopropyl groups is enhanced, causing the poly (N-isopropylacrylamide) to undergo a phase change, transforming into a hydrophobic state and a heterogeneous system. Therefore, when the poly (N-isopropylacrylamide) in the aqueous system is heated to about 36°C, the poly (N-isopropylacrylamide) will transform from a homogeneous system to a heterogeneous system. The invention utilizes the temperature-sensitive property of poly-N-isopropylacrylamide, and coats N-isopropylacrylamide and titanium dioxide together on the surface of the inner core of ketoprofen nanofiber to form a dense protective film layer, thereby preventing the effective ingredient of dexketoprofen tromethamine from being released into the gel system for protecting the dexketoprofen tromethamine drug-carrying fiber in a low-temperature storage state. When the plaster is used, it contacts the human body and the temperature rises, and the poly-N-isopropylacrylamide shrinks when it is transformed from a homogeneous system to a heterogeneous system, and the shell outside the inner core of the ketoprofen nanofiber gradually has pores and fails, so that the dexketoprofen tromethamine is gradually released.
[0053] Further preferably, S110 specifically includes: first mixing polyvinyl alcohol and half of the water in a first container according to a mass ratio of dexketoprofen tromethamine: first polyacrylic acid: polyvinyl pyrrolidone: ethanol: polyvinyl alcohol: water = (0.2-0.4): (8-12): (8-12): (16-20): (16-20): 100, then adding a uniform mixture of dexketoprofen tromethamine and ethanol into the first container for mixing, finally swelling the first polyacrylic acid and polyvinyl pyrrolidone in the other half of the water and adding them into the first container for mixing, magnetically stirring for 8h to 10h, and standing for 1.5h to 2h for degassing to obtain a core layer spinning solution.
[0054] Further preferably, S120 specifically includes: first mixing methyl cellulose, polylactic acid and hexafluoroisopropanol in a second container according to a mass ratio of titanium dioxide: chitosan: poly N-isopropylacrylamide: methyl cellulose: polylactic acid: water: hexafluoroisopropanol = (0.2-0.6): (4-6): (8-12): (8-12): (14-18): (40-50): 100, and then adding a uniform mixture of titanium dioxide, chitosan, poly N-isopropylacrylamide and water into the second container, mixing, magnetically stirring for 2h to 4h, and standing for 0.5h to 2h for degassing to obtain a shell spinning solution.
[0055] Further preferably, S130 specifically includes: injecting the core layer spinning solution and the shell layer spinning solution into a coaxial electrospinning device, controlling the injection flow rate of the core layer spinning solution to 0.7mL / h to 0.8mL / h, controlling the injection flow rate of the shell layer spinning solution to 0.3mL / h to 0.4mL / h, performing electrospinning under a voltage condition of 12kV to 14kV, receiving with tin foil at a receiving distance of 18cm to 20cm, and vacuum drying at room temperature for 18h to 24h after receiving, to obtain ketoprofen nanofibers.
[0056] In some implementations of the present invention, S200 specifically includes:
[0057] S210, using raw materials including ropivacaine, L-phenylalanine, a second polyacrylic acid, tetraethyl orthosilicate, ethanol and water, using hydrochloric acid as a catalyst, and obtaining a matrix sol through a sol-gel reaction.
[0058] Further preferably, S210 specifically includes: firstly mixing ropivacaine, tetraethyl orthosilicate and ethanol in a third container in a mass ratio of ropivacaine: L-phenylalanine: second polyacrylic acid: tetraethyl orthosilicate: ethanol: water = (1-1.5): (2-3): (6-8): (8-10): (30-35): 100, then adding a uniform mixture of L-phenylalanine, the second polyacrylic acid and water into the third container and mixing, adding an aqueous solution of hydrochloric acid to adjust the pH value to 4 to 5, and magnetically stirring for 3h to 4h to obtain a matrix sol.
[0059] It should be noted that the gel system used in the present invention is a silica inorganic gel. Accordingly, the present invention mixes ropivacaine, L-phenylalanine and ethyl orthosilicate, and prepares a sol containing ropivacaine and L-phenylalanine in a water-alcohol system under the action of an acidic catalyst.
[0060] In some implementations of the present invention, S300 specifically includes:
[0061] S310, mixing and dispersing the ketoprofen nanofibers in the matrix sol uniformly to obtain a ketoprofen sol;
[0062] S320, soaking the ketoprofen sol in anhydrous ethanol for aging for 30 to 36 hours, taking it out, washing it, and drying it to obtain a dexketoprofen tromethamine patch.
[0063] More preferably, in S310, the mass ratio of ketoprofen nanofibers to matrix sol is (40-60):100.
[0064] After obtaining the ketoprofen nanofibers and the matrix sol respectively, the present invention disperses the ketoprofen nanofibers in the matrix sol, and ages the sol containing the ketoprofen active ingredient into a gel. Finally, the gel is cut, sterilized, and packaged to obtain a plaster.
[0065] The matrix sol of the present invention also contains a certain amount of polyacrylic acid. Polyacrylic acid is a water-soluble macromolecular compound. When the polyacrylic acid molecule is dissolved in water, its side carboxyl group can be partially ionized into carboxylate ions, thereby carrying a negative charge. The shell layer of the ketoprofen nanofiber in the present invention contains positively charged chitosan. Therefore, the ketoprofen nanofiber can be effectively encapsulated by the aqueous gel system containing polyacrylic acid due to the electrostatic effect between the positive and negative charges, so that the ketoprofen nanofiber is uniformly and stably dispersed in the aqueous gel system of silicon dioxide and polyacrylic acid composite.
[0066] In addition, the raw materials of polylactic acid fibers mainly come from starch-containing agricultural products such as corn, wheat, and beets, which have good hydrophilicity. Therefore, ketoprofen nanofibers with polylactic acid added to the shell are more easily dispersed uniformly and stably in the aqueous gel system.
[0067] Compared with the aqueous polymer compound gel system, the inorganic gel system mainly based on silicon dioxide adopted in the present invention not only has higher mechanical strength, thermal stability and chemical stability, but also has poor compatibility with the organic ketoprofen nanofibers, so that the gel system of the present invention can effectively protect the dexketoprofen tromethamine drug-loaded nanofibers inside, and prevent the dexketoprofen tromethamine active ingredient from being released before being used.
[0068] Example 1
[0069] This embodiment provides a series of dexketoprofen tromethamine patch samples, and the raw material ratios used are shown in Table 1.
[0070] Table 1
[0071]
[0072] The process steps adopted are as follows:
[0073] S1, dexketoprofen tromethamine is stirred in ethanol at room temperature until it is completely dissolved; the first polyacrylic acid and polyvinyl pyrrolidone are stirred and mixed in half the mass of water to completely swell; polyvinyl alcohol and the remaining half the mass of water are mixed in a beaker, and then the uniform mixture of dexketoprofen tromethamine and ethanol is added to the first container for mixing, and finally the first polyacrylic acid and polyvinyl pyrrolidone after the mixed swelling are added to the first container for mixing; after mixing, magnetic stirring is turned on, and the rotation speed is stirred at 800 rpm / min for 8 hours to make the raw materials completely mixed and uniform, and the degassing is performed for 2 hours to obtain a core layer spinning solution;
[0074] S2, titanium dioxide, chitosan, poly (N-isopropylacrylamide) and water are mixed uniformly; methylcellulose, polylactic acid and hexafluoroisopropanol are mixed in a beaker, and then the uniform mixture of titanium dioxide, chitosan, poly (N-isopropylacrylamide) and water is added to the beaker for mixing; after the mixing is completed, the magnetic stirring is turned on, the stirring speed is 600 rpm / min for 2 hours, and the degassing is stopped for 0.5 hours to obtain the shell spinning solution;
[0075] S3, injecting the core layer spinning solution and the shell layer spinning solution into the coaxial electrospinning device, controlling the injection flow rate of the core layer spinning solution to 0.7 mL / h, controlling the injection flow rate of the shell layer spinning solution to 0.35 mL / h, performing electrospinning at a voltage of 12 kV, controlling the spinning temperature to 25±0.5°C, the humidity to 50±5%, receiving with tin foil at a receiving distance of 20 cm, and vacuum drying at room temperature for 24 h after receiving, to obtain ketoprofen nanofibers;
[0076] S4, uniformly mixing L-phenylalanine, the second polyacrylic acid and water; uniformly mixing ropivacaine, tetraethyl orthosilicate and ethanol in a beaker, then adding the uniform mixture of L-phenylalanine, the second polyacrylic acid and water into the beaker, adding 4wt% hydrochloric acid aqueous solution and stirring to adjust the pH value to 5, after the addition is complete, magnetically stirring at a speed of 300rpm / min for 4h to obtain a matrix sol;
[0077] S5. Shear and crush the ketoprofen nanofibers into short fibers of 0.1 mm to 0.15 mm, mix the ketoprofen nanofibers in the matrix sol, and disperse them evenly by ultrasonication to obtain ketoprofen sol; soak the ketoprofen sol in anhydrous ethanol for 36 hours, take it out, wash it twice with water and dry it to obtain a dexketoprofen tromethamine patch sample.
[0078] Comparative Example 1
[0079] This comparative example provides a series of dexketoprofen tromethamine patch samples, and the raw material ratios used are shown in Table 2.
[0080] Table 2
[0081]
[0082]
[0083] The process steps adopted are as follows:
[0084] S1, same as in Example 1, obtaining a core layer spinning solution;
[0085] S2, mixing chitosan, poly (N-isopropylacrylamide) and water uniformly; mixing methylcellulose, polylactic acid and hexafluoroisopropanol in a beaker, and then adding the uniform mixture of chitosan, poly (N-isopropylacrylamide) and water into the beaker for mixing; after mixing, turning on the magnetic stirring, stirring at a speed of 600 rpm / min for 2 hours, and standing for 0.5 hours for degassing to obtain a shell spinning solution;
[0086] S3, same as in Example 1, obtaining ketoprofen nanofibers;
[0087] S4, titanium dioxide, ropivacaine, L-phenylalanine, the second polyacrylic acid, sorbitol polyethylene glycol, gum arabic and N-methylpyrrolidone were uniformly mixed, and magnetically stirred at a speed of 300 rpm / min for 2 h to obtain a matrix sol;
[0088] S5. Shear and crush the ketoprofen nanofibers into short fibers of 0.1 mm to 0.15 mm, mix the ketoprofen nanofibers in the matrix sol, and disperse them evenly with ultrasound to obtain a dexketoprofen tromethamine patch sample.
[0089] Performance Testing
[0090] The paste-like dexketoprofen tromethamine patch samples 1 to 6 were cut into 4 cm × 4 cm and 0.3 cm thick, and subjected to in vitro permeation test on SD rat ex vivo skin. Complete and undamaged ex vivo skin samples were obtained from rats, and the residues were removed by washing with solvents and buffers. The skin samples were fixed in the permeation device, and the samples 1 to 6 to be tested were sent to the supply device to ensure that the samples were in contact with the ex vivo skin. The temperature was set at 36°C to simulate the in vivo environment. The test results are shown in Table 3.
[0091] Table 3
[0092]
[0093]
[0094] Dexketoprofen tromethamine paste samples 1 to 6 were cut into 10 cm × 10 cm pieces with a thickness of 0.5 cm, and were exposed to light for 96 hours at a temperature of 45 ± 1 ° C and a humidity of 80 ± 5% in a light box with a 1500 W white light source. The content change rate of ketoprofen after exposure to light was tested compared to the initial content, and the results are shown in Table 4.
[0095] Table 4
[0096] Serial number Sample 1 Sample 2 Sample 3 Sample 4 Sample 5 Sample 6 Relative content 98.65% 98.46% 98.31% 98.57% 92.62% 93.34%
[0097] Although the present invention is disclosed as above, the present invention is not limited thereto. Any person skilled in the art can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the protection scope of the present invention shall be subject to the scope defined by the claims.
Claims
1. A method for preparing a dexketoprofen tromethamine patch, characterized in that: The preparation method comprises: S100, preparing ketoprofen nanofibers by electrospinning using raw materials including dexketoprofen tromethamine, a first polyacrylic acid, poly-N-isopropylacrylamide, chitosan and titanium dioxide; S200, using raw materials including ropivacaine, L-phenylalanine, a second polyacrylic acid and tetraethyl orthosilicate to prepare a matrix sol by a sol-gel method; S300, mixing the ketoprofen nanofibers and the matrix sol, and performing gelation treatment to prepare the dexketoprofen tromethamine patch.
2. The preparation method according to claim 1, characterized in that: S100 specifically includes: S110, mixing raw materials including the dexketoprofen tromethamine, the first polyacrylic acid, polyvinyl pyrrolidone, ethanol, polyvinyl alcohol and water to obtain a core layer spinning solution; S120, mixing raw materials including the titanium dioxide, the chitosan, the poly (N-isopropylacrylamide), methylcellulose, polylactic acid, water and hexafluoroisopropanol to obtain a shell spinning solution; S130, injecting the core layer spinning solution and the shell layer spinning solution into a coaxial electrospinning device, and performing electrospinning to obtain the ketoprofen nanofibers; The inner core of the ketoprofen nanofiber contains the dexketoprofen tromethamine, and the outer wall contains the poly (N-isopropylacrylamide) and the titanium dioxide.
3. The preparation method according to claim 2, characterized in that: S110 specifically includes: first mixing the polyvinyl alcohol and half of the water in a first container according to a mass ratio of dexketoprofen tromethamine: first polyacrylic acid: polyvinyl pyrrolidone: ethanol: polyvinyl alcohol: water = (0.2-0.4): (8-12): (8-12): (16-20): (16-20): 100, then adding a uniform mixture of the dexketoprofen tromethamine and the ethanol into the first container for mixing, finally swelling the first polyacrylic acid and the polyvinyl pyrrolidone in the other half of the water and adding them into the first container for mixing, magnetically stirring for 8h to 10h, and standing for 1.5h to 2h for degassing to obtain the core layer spinning solution.
4. The preparation method according to claim 2, characterized in that: S120 specifically includes: firstly mixing the methyl cellulose, the polylactic acid and the hexafluoroisopropanol in a second container according to the mass ratio of titanium dioxide: chitosan: poly (N-isopropylacrylamide): methyl cellulose: polylactic acid: water: hexafluoroisopropanol = (0.2-0.6): (4-6): (8-12): (8-12): (14-18): (40-50): 100, then adding a uniform mixture of the titanium dioxide, the chitosan, the poly (N-isopropylacrylamide) and the water into the second container, mixing, magnetically stirring for 2h to 4h, standing for 0.5h to 2h for degassing, and obtaining the shell spinning solution.
5. The preparation method according to claim 2, characterized in that: S130 specifically includes: injecting the core layer spinning solution and the shell layer spinning solution into a coaxial electrospinning device, controlling the injection flow rate of the core layer spinning solution to be 0.7mL / h to 0.8mL / h, controlling the injection flow rate of the shell layer spinning solution to be 0.3mL / h to 0.4mL / h, performing electrospinning under a voltage condition of 12kV to 14kV, receiving the solution with tin foil at a receiving distance of 18cm to 20cm, and vacuum drying the solution at room temperature for 18h to 24h after receiving, to obtain the ketoprofen nanofibers.
6. The preparation method according to any one of claims 1 to 5, characterized in that S200 specifically includes: using raw materials including the ropivacaine, the L-phenylalanine, the second polyacrylic acid, the tetraethyl orthosilicate, ethanol and water, using hydrochloric acid as a catalyst, and obtaining the matrix sol through a sol-gel reaction.
7. The preparation method according to any one of claims 1 to 5, characterized in that S200 specifically includes: firstly uniformly mixing the ropivacaine, the tetraethyl orthosilicate and the ethanol in a third container according to the mass ratio of ropivacaine: L-phenylalanine: the second polyacrylic acid: tetraethyl orthosilicate: ethanol: water = (1-1.5): (2-3): (6-8): (8-10): (30-35): 100, then adding the uniform mixture of the L-phenylalanine, the second polyacrylic acid and the water into the third container for mixing, dropping the aqueous solution of hydrochloric acid to adjust the pH value to 4 to 5, and magnetically stirring for 3h to 4h to obtain the matrix sol.
8. The preparation method according to claim 6 or 7, characterized in that: S300 specifically includes: S310, mixing and dispersing the ketoprofen nanofibers in the matrix sol uniformly to obtain a ketoprofen sol; S320, soaking the ketoprofen sol in anhydrous ethanol for aging for 30 to 36 hours, taking it out, washing, and drying it to obtain the dexketoprofen tromethamine patch.
9. The preparation method according to claim 8, characterized in that: In S310 , the mass ratio of ketoprofen nanofibers to matrix sol is (40-60):
100.
10. A dexketoprofen tromethamine patch, characterized in that: The dexketoprofen tromethamine patch is obtained by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Ketoprofen gel and preparation method thereof
CN103156803A
Gel plaster containing ketoprofen and preparation method of gel plaster
CN110693860A
Ketoprofen patch and preparation method thereof
CN116747208A
Ketoprofen gel and preparation method thereof
CN118526444A
Nano-analgesic agent and preparation method thereof
CN102178663A